Assessment of Internal Radiation Dose in Gastro Intestinal Tract for Acute Ingestion of Ra-226 of the People of Bangladesh (Bangladesh Journal of Nuclear Medicine, 2018)
To design appropriate method for treatment planning it is necessary to know the precise radiation dose absorbed by any internal organ in human body. This paper will provide a method for calculating retention, absorbed dose, committed equivalent dose and committed effective doses due to acute ingestion of 1 Bq of Ra-226 in the gastro intestinal (GI) tract of Bangladeshi people for different age groups. Calculations are done by using “Internal Radiation Dose Assessment (IRDA)” software which has been developed in Visual Basic language. GI tract consists of four tissue compartments, e.g. stomach (ST), small intestine (SI), upper large intestine (ULI) and lower large intestine (LLI). One hour after the ingestion, the retention and absorbed dose show the trend ST > SI > ULI > LLI. For tissue compartments the variation of the committed equivalent dose pattern is LLI > ULI > ST > SI for the radionuclide. The variation of absorbed dose, committed equivalent dose and committed effective dose with respect to age follow the pattern: 1 year> 10years > adult female > adult male. The highest committed effective dose is found in the GI tract of 1 year old child. For other age groups these values are slightly less than those for 1 year old child.Bangladesh J. Nuclear Med. 19(1): 38-42, January 2016